Medication safety in Indonesia: Expanding pharmacists’ role through Interprofessional Education (IPE) and Interprofessional Practice (IPP) - Ernawati, Desak Ketut (Curtin University, 2015)
This study undertaken in Indonesia, examined how the pharmacist's role could be expanded into medication safety. It explored the feasibility of implementing interprofessional education as a means of fostering interprofessional practice. While also looking at pharmacy students' readiness to engage in interprofessional learning and graduates' perceptions of their preparedness to deliver patient care, a clinical pharmacy service pilot was also conducted to document need. Facilitators and barriers to education and practice change were also explored.